War Discourse and Disaster Premia - Hirshleifer, David,Mai, Dat,Kuntara Pukthuanthong (National Bureau of Economic Research, 2023)
Using a semi-supervised topic model on 7,000,000 New York Times articles spanning 160 years, we test whether topics of media discourse predict future stock and bond market returns to test rational and behavioral hypotheses about market valuation of disaster risk. Focusing on media discourse addresses the challenge of sample size even when major disasters are rare. Our methodology avoids look-ahead bias and addresses semantic shifts. War discourse positively predicts market returns, with an out-of-sample R2 of 1.35%, and negatively predicts returns on short-term government and investment-grade corporate bonds. The predictive power of war discourse increases in more recent time periods
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Mediale Berichterstattung; Zeitung; Krieg; Finanzkrise; Anlageverhalten; Investitionsentscheidung; Rentenmarkt; Aktienmarkt; Börsenkurs; Rendite; Risikoprämie; Wirtschaftsgeschichte; USA; Financial Crises; Behavioral Finance: Underlying Principles; General Financial Markets; General; Portfolio Choice; Investment Decisions; Contingent Pricing; Futures Pricing; Behavioral Finance; Role and Effects of Psychological; Emotional; Social; and Cognitive Factors on Decision Making in Financial Markets